IMPACT OF THIRD-PARTY FUNDS, FDR, AND NPF ON ROA OF INDONESIAN ISLAMIC BANKS - Anisa Ayuni; Zulfanda Riqsya Firizqi; Rachmania Nurul Fitri Amijaya (Airlangga International Journal of Islamic Economics and Finance, 2026)
This study aims to analyze the effects of Third-Party Funds (TPF), Financing to Deposit Ratio (FDR), and Non-Performing Financing (NPF) on Return on Assets (ROA) in Sharia Commercial Banks in Indonesia during the period August 2017 to July 2024. This study uses secondary data obtained from the Financial Services Authority (OJK) and analyzed using the Vector Error Correction Model (VECM) approach. The results show that TPF and FDR have a significant negative effect on ROA, while NPF has no significant effect. The policy implications suggest that Islamic bank management should implement more measured strategies in balancing fund collection and financing distribution, as well as strengthening liquidity risk mitigation to maintain profitability stability amid economic fluctuations.